Stabilization of residual soil using SiO2 nanoparticles and cement - Bahmani, Sayed Hessam; Kim Huat, Bujang; Asadi, Afshin; Farzadnia, Nima (Elsevier, 2014)
An experimental study was performed to determine the effect of SiO2 nanoparticles on consistency, compaction, hydraulic conductivity, and compressive strength of cement-treated residual soil. Also, SEM, XRD and FTIR tests were carried out to identify the underlying mechanisms. The addition of nanoparticles was found to advantageously affect the compactability, hydraulic conductivity. Besides, addition of 0.4% nanosilica to the cement treated soil improved the compressive strength by up to 80%. XRD, FTIR and SEM test results showed that silica nanoparticles promoted the pozzolanic reaction by transforming Portlandite into calcium silicate hydrate (C–S–H) gel.